Lakas sambayanan People power - Montano, Cesar; Apostol, Eugenia D.; Arroyo, Felicitas A.; Nolasco, Butch; Lacaba, Pete (Foundations for Worldwide People Power, 2002)
A video documentary on the history of People Power in the Philippines.